Effect of serum isoniazid level on treatment outcomes among tuberculosis patients with slow response – A retrospective cohort study. Issue 11 (November 2021) - Kim, Hyung Woo; Shin, Ah Young; Ha, Jick Hwan; Ahn, Joong Hyun; Kang, Hye Seon; Kim, Ju Sang
Abstract: Background: In this study, we investigate the effects of low serum TB drug level on treatment outcome among TB patients with slow response in South Korea, where the prevalence of rapid acetylator is relatively high. Methods: Among the pulmonary TB patients whose treatment outcomes were reported between 2014 and 2018 at Incheon St. Mary hospital, those who underwent TDM because of delayed culture conversion or reversion were included. Primary outcome was microbiological failure defined as (1) positive sputum culture after 120 days of treatment, or (2) culture-confirmed relapse within one year after treatment completion. Patients with culture conversion within 120 days and no relapse were classified as the final conversion group. Clinical characteristics and serum drug concentration at 2 h after administration (C2hr ) were compared between those two groups. Results: A total of 55 pulmonary TB patients were included. Prevalence of subtherapeutic range of C2hr for isoniazid and rifampin was 78.2% and 21.8%, respectively. With one year of follow-up, 21 cases were classified as the microbiological failure group, and 34 cases as the final conversion group. In a multivariable logistic regression model for predicting microbiological failure, C2hr of isoniazid was the most significant predictor after adjusting for the effects of age and sex (adjusted odds ratio, 0.29; p = 0.009). In a tree-based classification model, C2hr of isoniazid with cutoff level 2.5 μg/ml was the most important variable for predicting microbiological failure. Conclusions: Low serum isoniazid level was related to poor treatment outcomes among the TB patients with slow response.